2011
DOI: 10.1039/c1lc20236g
|View full text |Cite
|
Sign up to set email alerts
|

Lensless imaging for simultaneous microfluidic sperm monitoring and sorting

Abstract: 5.3 million American couples of reproductive age (9%) are affected by infertility, among which male factors account for up to 50% of cases, which necessitates the identification of parameters defining sperm quality, including sperm count and motility. In vitro fertilization (IVF) with or without intra cytoplasmic sperm injection (ICSI) has become the most widely used assisted reproductive technology (ART) in modern clinical practice to overcome male infertility challenges. One of the obstacles of IVF and ICSI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 34 publications
0
81
0
1
Order By: Relevance
“…Using this device, sperm motility and trajectories of motile sperm could be recorded. Subsequently, a lens-free, shadow-based, charge-coupled device (CCD) imaging system with a microfluidic chip was reported in 2011, and oligozoospermic and oligospermaesthenic cases were detected using trajectory analyses and sperm sorting with this system [31]. In 2015, Im et al developed a smartphone-based optical device that exploits diffraction patterns generated by microbeads following binding to biological targets, and detected human papillomavirus DNA.…”
Section: Smartphone-based Optical Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this device, sperm motility and trajectories of motile sperm could be recorded. Subsequently, a lens-free, shadow-based, charge-coupled device (CCD) imaging system with a microfluidic chip was reported in 2011, and oligozoospermic and oligospermaesthenic cases were detected using trajectory analyses and sperm sorting with this system [31]. In 2015, Im et al developed a smartphone-based optical device that exploits diffraction patterns generated by microbeads following binding to biological targets, and detected human papillomavirus DNA.…”
Section: Smartphone-based Optical Systemsmentioning
confidence: 99%
“…Thus, low-cost, portable devices for quantitative sperm analysis have been developed during the last decade [28][29][30][31][32][33][34]. Optical systems using these devices in sperm motility analyses are presented in Figure 2.…”
Section: Smartphone-based Optical Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A minimal image platform is desired to enable compactness, ease-of-use, minimized footprint, and portability to monitor sperm motility by a preclinical assay at home. Some researchers have developed a microfluidic chip that can be used by an individual himself at home on convenient moments to check his semen quality [56][57][58][59]. For example, if a person finds that his semen quality is low or that there are no motile sperm in his semen, he can opt for ICSI for his fertility treatment.…”
Section: Elastomer Chip Device For Analyzing Motility Of Motile Spermmentioning
confidence: 99%
“…Within the last decade, studies using PDMS microfluidic channels or funnels have suggested novel solutions for oocyte manipulation, sperm sorting, and embryo culture . Microfluidic systems that mimic oviductal structures and functions for use in RT are divided into those used for sperm motility control or monitoring [50][51][52][53][54][55][56][57][58][59][60], regulation of chemical gradients for in vitro fertilization and embryo culture [61][62][63][64][65][66][67][68][69], and applying mechanical stimuli to the developing embryo [70][71][72][73][74]. Although the unique characteristics of elastomers have been exploited for microstructure fabrication and/or micro-pumping, mechanical deformation of the elastomer membrane has not been used to produce new devices for RT.…”
Section: Microfluidic Channels To Handle Sperm and Embryosmentioning
confidence: 99%